Familial hypercholesterolemia in China half a century: A review of published literature. (March 2019) - Peng, Jie; Wu, Xue; Wang, Shilong; Zhang, Shuang; Wang, Xumin; Liu, Zesen; Hong, Jing; Ye, Pucong; Lin, Jie
Abstract: Aims: To investigate the status of familial hypercholesterolemia (FH) research and the characteristics of patients with FH in China. Methods: Published papers in Chinese or English language from PubMed, SinoMed and CNKI databases from 1971 to March 2018 were searched using 'Familial hypercholesterolemia', 'Chinese' and 'Han' as keywords. A systematic review of studies on familial hypercholesterolemia was then conducted. Results: A total of 391 articles were found, in which 22% were in English and 78% were in Chinese; approximately 43% are case reports and 34% are genetic reports according to the study type; 52% discussed the status of the disease and 11% investigated the subclinical status according to the study content. Furthermore, 96% of the articles were published by tertiary hospitals and 46% were conducted by cardiologists. The first expert consensus was issued in February 2018. Of the 163 case reports published before 2018, 48.7% used the Chinese FH clinical diagnostic criteria and 34.4% did not clearly indicate the diagnostic criteria. The incidence rates of low-density lipoprotein receptor ( LDLR ) and apolipoprotein B ( APOB ) mutations were 82% and 9%, and proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) mutations were rare in Chinese patients with FH. However, the data on lipid-lowering treatment rates, compliance rates and cardiovascular events in FH remain insufficient. Conclusions: Large-scale epidemiological investigation of FH has not been demonstrated, the recognition of FH remains rudimentary, and the guidelines are incomplete in China. The diagnosis and management of Chinese FH needs to be improved. Highlights: Familial hypercholesterolemia is a common hereditary disorder in china. Familial hypercholesterolemia is extremely underdiagnosed in china. Familial Hypercholesterolemia is undertreated in China.